Analysis of driver injury severity in wrong-way driving crashes on controlled-access highways. (September 2016) - Pour-Rouholamin, Mahdi; Zhou, Huaguo
Highlights: Factors associated with the injury severity of at-fault drivers involved in wrong-way driving (WWD) crashes were analyzed. A partial proportional odds (PPO) model was developed to quantify the effect of these parameter on injury severity. Based on the calculated average direct pseudo-elasticities, these factors were prioritized and several countermeasures were recommended. The performance of three ordered-response models was also explored. Abstract: For more than five decades, wrong-way driving (WWD) has been notorious as a traffic safety issue for controlled-access highways. Numerous studies and efforts have tried to identify factors that contribute to WWD occurrences at these sites in order to delineate between WWD and non-WWD crashes. However, none of the studies investigate the effect of various confounding variables on the injury severity being sustained by the at-fault drivers in a WWD crash. This study tries to fill this gap in the existing literature by considering possible variables and taking into account the ordinal nature of injury severity using three different ordered-response models: ordered logit or proportional odds (PO), generalized ordered logit (GOL), and partial proportional odds (PPO) model. The findings of this study reveal that a set of variables, including driver's age, condition (i.e., intoxication), seatbelt use, time of day, airbag deployment, type of setting, surface condition, lighting condition, and type of crash, has a significant effect on the severity of a WWD crash. Additionally, a comparison was made between the three proposed methods. The results corroborate that the PPO model outperforms the other two models in terms of modeling injury severity using our database. Based on the findings, several countermeasures at the engineering, education, and enforcement levels are recommended.